Association of Heavy Metals and Selenium Content in Rice with Incidence of Esophageal Cancer in Golestan Province, Iran - Hadi Rahimzadeh; Mahdi Sadeghi; Somayeh Beirami; Abotaleb Bay; Morteza Mansurian; Gholamreza Roshandel (Golestan University Of Medical Sciences, 2017)
ABSTRACT Introduction: Heavy metals have an important role in human health because of their nutritive value and possible adverse effects. The objective of this study was to assess level of heavy metals and selenium in rice harvested in the Golestan Province, Iran. Materials and Methods: This study was conducted in the Golestan Province, northern Iran. The area under rice cultivation is 45714 acres. Overall, 69 rice samples were collected from rice farms in different areas of the province including high-risk (42 samples) and low-risk areas (27 samples) for esophagus cancer (EC). Concentrations of heavy metals were measured by polarograph. Voltammetric analysis was carried out using 797 VA computrace (Metrohm). Results: Maximum concentrations of zinc, cadmium, lead, copper, nickel, cobalt and selenium in high-risk areas for EC were 70.6, 0.41, 5.05, 14.4, 8.8, 0.88 and 0.48 mg/kg as dry weight, respectively. Maximum concentrations of these elements in the low-risk area for EC were 88.4, 0.37, 3.9, 17.2, 8.1, 0.27 and 0.25 mg/kg as dry weight, respectively. The concentration of Se in high-risk areas were significantly higher than that in low-risk areas (P<0.05). Conclusions: Heavy metals and Se may act as possible risk factors for EC in the Golestan Province, which should be considered when designing cancer control programs in this area. KEYWORDS: Heavy metal, Rice, Golestan province, Esophageal Cancer